Exploring The Associated Factors Of Depression, Anxiety, And Stress Among Healthcare Shift Workers During The Covid-19 Pandemic - Norsham Juliana; Nor Amira Syahira Mohd Azmi; Nadia Mohd Effendy; Nur Islami Mohd Fahmi Teng; Sahar Azmani; Nizam Baharom; Aza Sherin Mohamad Yusuff; Izuddin Fahmy Abu (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA